A (in)visibilidade de um objeto romano do Museu Nacional de Arqueologia. Leituras de história da ciência - Elisabete J. Santos Pereira; Maria de Fátima Nunes (Midas: Museus e Estudos Interdisciplinares)
From the 1980s, researchers in the history of science field have approached scientific objects as primary research sources, revealing an innovative perspective about the local and global relations in knowledge production. Scientific objects reflect the technologies and contexts involved in knowledge production, and the range of economic, cultural, social and intellectual factors at work in societies. The study of scientific objects can also reveal the social and scientific dynamics that enabled individuals to collect objects and create museum collections, and their role in founding and developing museums; furthermore, it provides a deeper understanding about the role of the individuals that produced knowledge about the past, that established networks for communication, exchange and knowledge dissemination throughout the western world. This article outlines a single object biography, a roman archaeological artefact – a silver and gold patera (2nd – 1st century AD) – that is part of the Museu Nacional de Arqueologia (MNA) collections since 1905. This approach highlights the potentialities of this methodology applied to the history of museological institutions, in this case archaeology museums.